Entomological Reference Collection: 85 years of contributions to public health - Dolci, Mariana de Carvalho; Spina, Fabrício Auad; Sallum, Maria Anice Mureb (Revista de Saúde Pública, 2023)
The Department of Hygiene of the Faculty of Medicine of São Paulo (FMUSP), organized with the support of the Rockefeller Foundation, became the Institute of Hygiene, with the inaugural class taught by Samuel Darling in 1918. The history of Public Health Entomology is mixed with that of the Institute itself, which became the Faculty of Hygiene and Public Health in 1945. Still in the 1930s, Paulo César de Azevedo Antunes and John Lane organized Public Health Entomology within the Medical Parasitology area of the then Institute of Hygiene. During this period, the entomology laboratory came to be recognized for its research in the systematics of hematophagous insects, as well as in the ecology, biology and behavior of vectors. The Entomological Reference Collection (CER) originated naturally from the research of Paulo César Antunes and John Lane and is a national and international heritage covering primary and secondary types of insect species that are of interest to public health. Over the years, it has been consolidated with the efforts of Augusto Ayroza Galvão, Renato Corrêa, José Coutinho, Nelson Cerqueira, Ernesto Rabello, Oswaldo Forattini and others. In its over eighty years of activities, CER has enabled the training of several scientists able to act in programs of surveillance and control of endemic diseases associated with insect vectors throughout Latin America, in addition to training taxonomists focused on insects of interest in Public Health. Researchers from other Brazilian institutes and abroad joined the entomology laboratory because of its importance and the research developed in it. The growing scientific production made it possible for entomological studies developed at the Faculty of Public Health (FSP) to gain international visibility, contributing to the development of disease prevention and epidemic control actions in the country.